Post-Covid-19 Syndrome: Improvements in Health-Related Quality of Life Following Psychology-Led Interdisciplinary Virtual Rehabilitation - Sari Harenwall; Suzanne Heywood-Everett; Rebecca Henderson; Sherri Godsell; Sarah Jordan; Angela Moore; Ursula Philpot; Kirsty Shepherd; Joanne Smith; Amy Rachel Bland (SAGE Publishing, 2021)
Coronavirus disease 2019 (COVID-19) is increasingly recognized as having significant long-term impact on physical and mental health. The Primary Care Wellbeing Service (PCWBS) in Bradford District Care NHS Foundation Trust (BDCFT) is a psychology-led specialist interdisciplinary team of health professionals specializing in persistent physical symptoms (PPS) and Chronic Fatigue Syndrome (CFS)/Myalgic Encephalomyelitis (ME) with an emphasis on holistic integrated care. The PCWBS quickly recognized the risk of the long-term effects of COVID-19, particularly for social, health and care staff, and developed a 7-week virtual rehabilitation course which was piloted in October 2020. The " Recovering from COVID " course takes a whole system, biopsychosocial approach to understanding COVID-19 and post-viral fatigue (PVF) and is delivered by an interdisciplinary team consisting of a clinical psychologist, physiotherapist, occupational therapist, dietitian, speech and language therapist, assistant psychologist, and a personal support navigator with support from a team administrator. The course focuses on understanding PVF, sleep optimization, nutrition, swallowing, activity management, energy conservation, stress management, breathing optimization, managing setbacks, and signposting to appropriate resources and services. Since the pilot, PCWBS has delivered 7 courses to support over 200 people suffering from post-COVID-19 syndrome. One hundred and forty-nine individuals that enrolled on the " Recovering from COVID " course completed the EQ-5D-5L to assess Health-related quality of life (HRQoL) across 5 dimensions, including problems with mobility, self-care, usual activities, pain/discomfort, and anxiety/depression. Subsequently, 76 individuals completed these measures at the end of the rehabilitation course showing that patient ratings were significantly improved. In response to the NIHR recommendation for rapid evaluation of different service models for supporting people with post-COVID-19 syndrome, this data offers hope that rehabilitation is effective in reversing some of the problems faced by people living with the long-term effects of COVID-19.